2019
DOI: 10.3390/c5030056
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Chained Carbon: Recent Ab Initio Studies

Abstract: Carbon chains or carbyne-like structures represent the next generation of 1D materials whose properties can be tuned by the chain length, doping, and the type of termination. Currently inaccessible technology of the macroscopic carbyne synthesis and characterization makes theoretical work especially valuable. The state of the art methods being applied in the field are density functional theory and molecular dynamics. This paper provides a review of the current state of research on modeling linear carbon struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Isolated carbon species: short chains with different terminal groups, 5 long confined chains, 6 and even closed carbon loops 7 have been obtained and studied numerically. 8 However, it is yet a challenge to synthesize a macroscopic amount of crystalline carbyne, which has at least two variations with cumulene (double bonds CC) or polyyne (alternating single and triple bonds −CC−) chains. Argon beamstimulated plasma-enhanced synthesis technology 9 was proposed more than 20 years ago for production of crystalline linear-chained carbon (LCC) films, hundreds of nanometers thick with hexagonal chain packing and an interchain distance of 5 Å.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated carbon species: short chains with different terminal groups, 5 long confined chains, 6 and even closed carbon loops 7 have been obtained and studied numerically. 8 However, it is yet a challenge to synthesize a macroscopic amount of crystalline carbyne, which has at least two variations with cumulene (double bonds CC) or polyyne (alternating single and triple bonds −CC−) chains. Argon beamstimulated plasma-enhanced synthesis technology 9 was proposed more than 20 years ago for production of crystalline linear-chained carbon (LCC) films, hundreds of nanometers thick with hexagonal chain packing and an interchain distance of 5 Å.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Isolated carbon species: short chains with different terminal groups, long confined chains, and even closed carbon loops have been obtained and studied numerically . However, it is yet a challenge to synthesize a macroscopic amount of crystalline carbyne, which has at least two variations with cumulene (double bonds CC) or polyyne (alternating single and triple bonds −CC−) chains.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are two common nite chain allotropes: 2 polyynes, with alternating single and triple carbon bonds reected in alternating bond lengths, and cumulenes, which have one repeated double bond. 1 The properties of these carbon chain structures are currently under intensive study 1,[3][4][5][6][7] along with their potential applications, such as nanoelectronics, spintronics, and nonlinear optics. 1,4,5 Carbon chains can be synthesized in solution with lengths of tens of atoms before being crystallized.…”
mentioning
confidence: 99%
“…1 The properties of these carbon chain structures are currently under intensive study 1,[3][4][5][6][7] along with their potential applications, such as nanoelectronics, spintronics, and nonlinear optics. 1,4,5 Carbon chains can be synthesized in solution with lengths of tens of atoms before being crystallized. 1 However, because of their strong reactivity, protecting them is necessary, e.g., with specic end-groups.…”
mentioning
confidence: 99%
“…The reported results showed that a combination of substrate structure and terminal group type of the carbon chain influences the work function of the material, a property exploitable both for the electronic and sensing applications of these systems. A review of the properties of this novel material was reported in [9] summarizing the theoretical predictions of its unique properties and a comparison with available experimental data.…”
mentioning
confidence: 99%